Unplanned Readmission Is Associated With Decreased Overall Survival and Performance After Metastatic Spine Surgery. Issue 9 (1st May 2023) - Chanbour, Hani; Chen, Jeffrey W.; Gangavarapu, Lakshmi S.; Bendfeldt, Gabriel A.; LaBarge, Matthew E.; Ahmed, Mahmoud; Roth, Steven G.; Chotai, Silky; Luo, Leo Y.; Abtahi, Amir M.; Stephens, Byron F.; Zuckerman, Scott L.
Abstract : Study Design: Retrospective case-control study. Objective: In a cohort of patients undergoing metastatic spine surgery, we sought to: (1) identify risk factors associated with unplanned readmission, and (2) determine the impact of an unplanned readmission on long-term outcomes. Summary of Background Data: Factors affecting readmission after metastatic spine surgery remain relatively unexplored. Materials and Methods: A single-center, retrospective, case-control study was undertaken of patients undergoing spine surgery for extradural metastatic disease between 02/2010 and 01/2021. The primary outcome was 3-month unplanned readmission. Preoperative, perioperative, and tumor-specific variables were collected. Multivariable Cox regression was performed, controlling for tumor size, other organ metastasis, and preoperative/postoperative radiotherapy/chemotherapy. Results: A total of 357 patients underwent surgery for spinal metastases with a mean follow-up of 538.7±648.6 days. Unplanned readmission within 3 months of surgery occurred in 64/357 (21.9%) patients, 37 (57.8%) were medical, 27 (42.2%) surgical, and 21 (77.7%) were related to their spine surgery. No significant differences were found regarding demographics and preoperative variables, except for insurance, where most readmitted patients had private insurance compared with nonreadmitted patients ( P =0.021). No significant difference was found in preoperative radiotherapy/chemotherapy. Regarding perioperative exposure variables, readmitted patients had a higher rate of postoperative complications (68.8% vs. 24.2%, P <0.001) and worse postoperative Karnofsky Performance Score ( P =0.021) and Modified McCormick Scale ( P =0.015) at the time of first follow-up. On multivariate logistic regression, postoperative complications were associated with increased readmissions (odds ratio=1.38, 95% CI=1.25–1.52, P <0.001). Regarding the impact of unplanned readmission on long-term tumor control, unplanned readmission was associated with shorter time to local recurrence (log-rank; P =0.029) and reduced overall survival (OS) (log-rank; P <0.001). On multivariate Cox regression, other organ metastasis [hazard ratio (HR)=1.48, 95% CI=1.13–1.93, P =0.004] and 3-month readmission (HR=1.75, 95% CI=1.28–2.39, P <0.001) were associated with worsened OS, with no impact on LR. Postoperative chemotherapy was significantly associated with longer OS (HR=0.59, 95% CI=0.45–0.77, P <0.001). Conclusions: Postoperative complications were associated with unplanned readmission following metastatic spine surgery. Furthermore, 3-month unplanned readmission was associated with a shorter time to local recurrence and decreased OS. These results help surgeons understand the drivers of readmissions and the impact of readmissions on patient outcomes. Level of Evidence: 3.